Particle size characteristics of buriti oil microcapsules produced by gelatin-sodium alginate complex coacervation: Effect of stirring speed - Lemos, Yuri Pessoa [UNESP]; Mariano Marfil, Paulo Henrique; Nicoletti, Vânia Regina [UNESP] (Taylor & Francis, 2017)
The influence of hydrodynamic conditions in the coacervation medium of the carotenoid-rich buriti oil using gelatin-alginate as wall materials was investigated. The stirring speed had strong influence on the size of the microcapsules, and Reynolds number higher than 70000 resulted in particle size D[4,3] lower than 200 μm. The carotenoid encapsulation efficiency was around 80%, with freeze-dried particles presenting intense yellow color. Although the size of the microparticles was highly dependent on the hydrodynamic conditions during coacervate formation, complex coacervation of gelatin and sodium alginate showed to be a feasible process to producing buriti oil microcapsules.
Keywords: Agitation; Carotenoids; Color; Encapsulation efficiency; Reynolds number